Revealing the role of cancer-associated fibroblast senescence in prognosis and immune landscape in pancreatic cancer - Luyao Liu; Hai Huang; Bin Cheng; Huaping Xie; Wang Peng; Haochen Cui; Jingwen Liang; Mengdie Cao; Yilei Yang; Wei Chen; Ronghua Wang; Yuchong Zhao (iScience)
Summary: Cancer-associated fibroblasts (CAFs) represent a major contributor to tumor growth. Cellular senescence is a state of cell-cycle arrest characterized by a pro-inflammatory phenotype. The potential impact of CAF senescence on tumor progression and the tumor microenvironment (TME) remains to be elucidated. Here, we systematically investigated the relationship between CAF senescence and the TME of pancreatic ductal adenocarcinoma (PDAC) based on multi-omics analysis and functional experiments. CAF senescence promotes tumor progression in vitro and in vivo and contributes to the formation of immunosuppressive TME. A CAF-senescence-related risk score was developed to predict overall survival, immune landscape, and treatment sensitivity in patients with PDAC. Further experiments revealed that plasminogen activator urokinase (PLAU) derived from senescent CAFs (SCAFs) promoted PDAC progression and was involved in immunosuppression. Together, these findings suggested that CAF senescence was correlated with tumor progression, and the CAF-senescence-based machine learning model could potentially predict prognosis in patients with PDAC.